2018
DOI: 10.1136/rmdopen-2018-000695
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis approach to the relationship between patient and physician global assessments of rheumatoid arthritis activity

Abstract: ObjectivePatients and physicians commonly differ in their assessments of rheumatoid arthritis (RA) activity. Clinically meaningful discordance thresholds or validation of their ability to predict functional outcomes are lacking. We explored whether an unbiased, person-centred latent profile analysis (LPA) approach could classify cases based on patient global assessment (PtGA) and physician global assessment (MDGA) assessments of RA activity. We further examined whether the LPA groups displayed greater differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Still, one may ask if the PGA should be included at all in a definition of remission of inflammation, since functional outcomes, for whatever reason are worse, independent of differences in radiographic progression. Other studies have, however, shown that the HAQ has only a minor influence on PGA score, suggesting there is little reverse causation, whereas pain is the greatest driver of PGA 20 38. This integration of patient-derived factors and more objective markers provides a robust overall assessment of disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, one may ask if the PGA should be included at all in a definition of remission of inflammation, since functional outcomes, for whatever reason are worse, independent of differences in radiographic progression. Other studies have, however, shown that the HAQ has only a minor influence on PGA score, suggesting there is little reverse causation, whereas pain is the greatest driver of PGA 20 38. This integration of patient-derived factors and more objective markers provides a robust overall assessment of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off beyond 2 cm would not only jeopardise agreement with the index definition and be associated with poorer long-term function but also require other factors to be considered. While mostly pain and partly fatigue influence PGA irrespective of disease activity,38 pain and fatigue may also reflect active inflammation and thus disease activity in many patients 46…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, discordance between patient and physician assessment of RA has been reported in over a third of RA patients, with patients with discordance typically reporting a higher level of disease activity than their physicians [ 14 , 16 ]. Such discrepancies have been shown to negatively impact therapeutic outcomes [ 9 ], with discordance contributing to worse HRQoL, activity impairment, and reduced work productivity [ 17 , 18 ]. Pain appears to be the most important domain to patients, whereas Physician Global Assessment of Arthritis (MDGA) is driven by physician-assessed measures of swollen and tender joint counts (SJC and TJC, respectively) and levels of inflammation markers [ 9 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing sick leave only among employed patients: 43/46 (93%)18–22 24–27 29 31–39 42–47 50–56 58–60 63 65–69 71 73…”
Section: Methodsmentioning
confidence: 99%
“…Assessing presenteeism among employed patients that were not in sick leave: 37/40 (90%)18–22 24–26 31–39 42 43 50–56 58–60 62–64 67–69 71 73…”
Section: Methodsmentioning
confidence: 99%